A Method to Introduce Building Performance Simulation to Beginners - Niko Gentile; Jouri Kanters; Henrik Davidsson (Energies, 2020)
Competence in performing Building Performance Simulations (BPS) is a fundamental asset for an energy specialist. However, teaching BPS to new students can be challenging, often due to the overwhelming capabilities of the software. The consequences for students are frustration and lack of confidence using the software, dividing group work based on previous expertise and, most importantly, the inability to predict and critically analyse results due to the superficial understanding of simulations. This paper presents and evaluates a simple method named ‘control method’ which is intended to introduce BPS in classes where students have a limited experience working with BPS, significantly different educational backgrounds, and where the time to teach BPS in class is limited. The method is built around the Structure of Observed Learning Outcomes taxonomy. It aims to provide the students with a basic understanding of the input-output relationship between parameters, prompting the use of BPS independently during their individual study time. The application of the method is evaluated with two survey-based studies. The findings suggest that the method prompts higher level thinking in BPS and collaborative learning in groups. Further investigation is needed to verify if students’ ability to predict results is also increased.